Potato variety diversity, determinants and Implications for potato breeding strategy in Ethiopia - Kolech, S.A.; Halseth, D.; Jong, W. de; Perry, K.; Wolfe, D.; Tiruneh, F.M.; Schulz, S. (Springer, 2015)
Understanding what farmers need in potato varieties and assessing available genetic resources at the farmer and district levels is important for the conservation and improvement of potato in Ethiopia. A survey was conducted in six major potato growing districts representing different agro-ecologies, cropping systems, market outlets, and levels of new variety adoption. Seventy to ninety percent of the farmers surveyed reported growing two or more potato varieties; some farmers reported growing up to five. The greatest diversity at the district level (up to 10 potato varieties) was recorded at Gumer & Geta where there is better access to new varieties while the lowest diversity was reported in districts with low access to new cultivars. The distribution of varieties differed among agro-ecologies as did the traits that farmers were most concerned with, such as drought tolerance, late blight resistance, yield potential, marketability, food value, storage quality, adaptation to low soil fertility, time to maturity and suitability for multiple harvesting. Farmers’ decision-making processes and external factors that influence potato variety diversity were also documented. The registration of predominant local varieties and use of these local varieties as a starting point for the development of improved varieties are some of the recommendations for future potato breeding in Ethiopia. Moreover, it is necessary to consider variations in agro-ecologies, cropping systems and market outlets in the process of developing varieties suitable for farmers’ and consumers’ real needs.